2017
DOI: 10.2140/pjm.2017.290.403
|View full text |Cite
|
Sign up to set email alerts
|

The ambient obstruction tensor and conformal holonomy

Abstract: Many institutions now require or encourage their researchers to deposit published articles in their institutional repositories. MSP cooperates with this requirement by sending authors or librarians, upon demand, a version of the published file suitable for the purpose. We request that you use the final published version and not a preprint or postprint version, which are not considered definitive. October 2017 Pacific Journal of Mathematics THE AMBIENT OBSTRUCTION TENSOR AND CONFORMAL HOLONOMY THOMAS LEISTNER … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…And thus the well-definedness of the Cauchy problem implies the existence of an associated (n + 1)-dimensional Lorentzian with a parallel spinor. Such a relation between families of metrics with special holonomy and solutions of the constraint equations was already conjectured by Leistner and Lischewski, see [27]. We essentially show that the conditions in [27, Table 1] is satified if and only if the divergence condition (31) in our Appendix D is satisfied.…”
Section: Manifold Metric Dimension Typesupporting
confidence: 72%
See 2 more Smart Citations
“…And thus the well-definedness of the Cauchy problem implies the existence of an associated (n + 1)-dimensional Lorentzian with a parallel spinor. Such a relation between families of metrics with special holonomy and solutions of the constraint equations was already conjectured by Leistner and Lischewski, see [27]. We essentially show that the conditions in [27, Table 1] is satified if and only if the divergence condition (31) in our Appendix D is satisfied.…”
Section: Manifold Metric Dimension Typesupporting
confidence: 72%
“…Important progress about Lorentzian manifolds with parallel spinors was recently achieved by H. Baum, Th. Leistner and A. Lischewski [8,28,27], see also [9] for associated lecture notes. In particular, these authors showed the well-posedness of an associated Cauchy problem which we will now describe in more detail and which will be the main topic of the present article.…”
Section: The Cauchy Problem For Parallel Light-like Spinorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial data triples are also tightly connected to a Cauchy problem for parallel spinors on Lorentzian manifolds, recently studied by Baum, Leistner and Lischewski [9,8,35,36], see also [44]. Obviously the work by Baum, Leistner, and Lischewski is tightly connected to Leistner's work on holonomy groups of Lorentzian manifolds [34].…”
Section: Results Of This Articlementioning
confidence: 92%
“…We will prove this theorem in Section 2.4. Note that the statement about the obstruction tensor can also be obtained from results in [23]. Theorem 1.2 leads us to study the equation (1.2) for g as in (1.1) defined by a Walker metric g with parallel null distribution N and with a tensor h with Im(h) ⊂ N .…”
Section: Introduction and Main Resultsmentioning
confidence: 96%